Salads are more than leaves : salads to get excited about - Silcock, Elena (Hamlyn, 2022)
"For too long salads have languished on the sidelines of dining tables, reduced to mere accompaniments or starters, but what if we gave salads the limelight they deserve? [This book] showcases dishes that are big on flavour, texture and impact. Featuring sections on building your salad, maximising flavour and plating to impress, you'll find over 80 recipes for salads to fit every season, mood, and occasion, plus substitute options for vegans and vegetarians and suggestions for how to group salads together for a larger salad party"--Page [4] of cover.